Uji Efektifitas Filtrat Buah Merah terhadap Penurunan Kadar Kholestrol Metode Chod-Pap pada Telur Burung Puyuh - Prafiadi, Sigit; Maturahmah , Enik (Syntax Literate, 2025)
This study aims to determine the effectiveness of red fruit filtrate (Pandanus concideus Lam) on the reduction of cholesterol content in quail eggs (Coturnix japonica). The data from the research results can be used as reference material for food health. This study is a truly experimantal design or actual experiment in the laboratory and the design follows a complete random design (RAL) with 5 treatments of red fruit filtrate concentrations (Pandanus concideus Lam), namely 20%, 30%, 40%, 50%, and control treatment using aquades that are not given treatment. Based on the One Way anova test, the results obtained showed a significant decrease in total cholesterol levels in quail eggs with a Fcal value greater than Ftabel and a probability value of 0.00 below the significant level (α) = 0.05. Based on the ducan test, it was obtained that the concentration of filtrate 40% and 50% had the same effect and was the most effective in lowering cholesterol levels, compared to the concentrations of 30% and 20% which showed different effects in reducing cholesterol content in quail eggs, so it can be said that red fruit filtrate has an effect in lowering cholesterol in quail eggs (yolk)